Membangun Ketahanan Pangan Terhadap Budidaya Ayam Kampung Golden - Irwanto, Tito; Aprizal, M.Irpan; HANUARSYAH , DWI; RAFSANJANI, RIKEI; NOVRIANDA, HERRY (Universitas Dehasen Bengkulu, 2023)
Local chickens have great potential to be developed into superior seeds in an effort to support food security and improve the welfare of farmers, in Indonesia there are reportedly 32 local chicken species. Local chickens are more resistant to diseases, especially avian influenza (AI) or bird flu, than purebred chickens because they have a higher percentage of antiviral genes (Mx +), so it is done by utilizing available resources. including through the utilization of yard land by cultivating Golden type native chickens in RT.03, RW.03 Betungan Village, Selebar Subdistrict, Jalan A.Khalik. The method of implementing our community service which is used for the cultivation of golden type native chickens in maintaining food security is patterned after counseling and mentoring, Thus in applying the community service program, we carry out golden native chicken cultivation activities, The purpose of this activity is to provide insight, knowledge and skills in the use of more modern technology in the form of utilizing land to be used as a rearing cage, for breeding, raising chickens, and selling chickens of all ages. In addition to fulfilling animal protein needs for the household scale, it can also increase residents' income by selling. The sale can be through various social media such as WhatApp Group, Facebook, Instagram, and Tiktok so that it is hoped that it will revive the economy of RT.03, RW.03 Jalan A.Khalik, Betungan Village, Selebar District and it is hoped that residents around RT3 can follow the golden chicken cultivation.